Failure mechanism of layer-crack rock models with different vertical fissure geometric configurations under uniaxial compression - Tong-bin Zhao; Wei-yao Guo; Yun-liang Tan; Feng-hai Yu; Bin Huang; Lian-sheng Zhang (Advances in Mechanical Engineering, 2017)
Many case studies have revealed that rock bursts generally occur in high stress concentration areas where layer-crack structures often exist, especially for brittle coal or rock masses. Understanding the mechanical behavior of layer-crack rocks is beneficial for rational design and stability analysis of rock engineering project and rock burst prevention. This study numerically investigated the influence of vertical fissure geometric configurations on the mechanical behavior of layer-crack rock models through uniaxial compression tests. Results reveal that the deformation and strength behaviors of layer-crack specimens depend on the vertical fissure geometric configurations, which also influence the crack evolution process. In aspect of failure mode, it is splitting failure or shear failure of the whole layer-crack specimen when the fissure length is smaller than 40 mm, but it is splitting failure or shear failure of supporting bodies in other conditions. Among the three factors, the influencing degree in order from strong to weak is fissure number, fissure length, and fissure width. Meanwhile, the influence of fissure geometric configurations on the failure mechanism of layer-crack structure and the occurrence mechanism of rock burst were revealed. In addition, some advices for keeping the stability of layer-crack structure and mitigating rock bursts were given.